Profile of Musculoskeletal Tumor in Saiful Anwar General Hospital Malang from January 2011 until December 2018 - Istan Irmansyah Irsan; Satria Pandu Persada Isma; Abdul Aziz; Muhammad Hilman Bimadi; I Gusti Ngurah Arga Aldrian Oktafandi (Berkala Kedokteran, 2020)
Abstract: Musculoskeletal tumors are relatively rare, with 0.2%-0.5% of all malignant tumors in all ages. The geographic distribution of musculoskeletal tumors varies significantly around the world. This study aims to describe the musculoskeletal tumor profile in Saiful Anwar General Hospital. All data were obtained from the department of orthopaedic and traumatology database, Saiful Anwar general hospital. Thus, patients who were diagnosed with either bone tumor or soft tissue tumor between January 2011 to December 2018 were selected for the present study. The clinical-pathological conference (CPC) was carried out to ensure the validity of all the registered data. A total of 577 patients with tumors from January 2011 to December 2018 was obtained. Out of all the cases, 439 (76%) cases are bone tumors, and the remaining 138 (24%) cases are soft tissue tumors. The most frequent locations of the musculoskeletal tumors are the long bones of the thigh and lower leg. This study shows an increasing trend in musculoskeletal tumors incidence, despite decreasing numbers in several years. This result goes along with a rising trend in malignancy cases with a higher amount compared to the benign one. Moreover, MBD and osteosarcoma were found to be the most common tumor and primary bone tumors, respectively. However, the fact that there is some data loss in the study limited the study for a more accurate result.   Keywords: Musculoskeletal tumor; Bone tumor; Osteosarcoma; Malang; East Java